Production of Water-Soluble Chitosan from Crab Shells (Portunus sp.) by Pressurized Hydrolysis Method as an Active Material for Hand Sanitizer - Dharmayanti, Niken; Natalia, Dessy A; Permadi , Aef; Dewi, Fera R; Thongsamouth, Khamhou (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research Water-soluble chitosan from crab’s shell can be produced via the pressurized hydrolysis method in an acidic environment with a pressure cooker; the optimal treatment is a 3% HCl concentration. Water-soluble chitosan from crab’s shell has the following properties: it is yellowish white in color, odorless, powder-like, with a yield of 83.37±0.73, an acidity degree of 5, 83±0.34, viscosity of 69.0±0.82, solubility of 93.57±0.33, and a degree of deacetylation of 78.4%. The optimal concentration for water-soluble chitosan from crab’s shell inhibition is 160 mg/ml, with an inhibition zone of 7.47 mm for S. aureus and 6.70 mm for E. coli, falling in the medium category. Physical features of organoleptic water-soluble chitosan from crab’s shell hand sanitizer: neutral appearance (5), somewhat similar fragrance (6), neutral texture (5), similar (6), not homogenous, dispersion 3.59-4.03 cm, pH 6.05-6.28. The most effective hand sanitizer formulation from crab’s shell water soluble chitosan is HS3 (including 200 mg/ml of water-soluble chitosan), which has a weak inhibition zone of 5.35±0.57 mm for S. aureus bacteria and 4.70±0.07 mm for E. coli. Abstract There has been no research on the application of water-soluble chitosan (WSC) derived from crab shells as a hand sanitizer. using a pressurized hydrolysis method. The limited solubility of chitosan at neutral pH restricts its usability. The aim of this study was to produce WSC from crab shells using pressurized hydrolysis methods as an active ingredient for hand sanitizer. Chitosan was depolymerized into WSC by utilizing hydrochloric acid (2, 3, and 4%) and was hydrolyzed using a pressure cooker at a temperature of approximately 110˚C for 1 hour. Isopropyl alcohol was then added to the filtrate at a ratio of 2:1. The selected WSC was treated with 3% HCl and made into 3 different concentrations of 140, 150, and 160 mg/ml, then tested for its antibacterial activity. The WSC hand sanitizer antibacterial test has concentrations of 180, 190 and 200 mg/ml, and for positive control using commercial hand sanitizer, and negative control in the form of basic gel without chitosan. By depolymerizing chitosan using 3% HCl, a high solubility (93.57±0.33) of WSC was achieved, with a degree of deacetylation (DD) value of 78.4%. The results indicated that the concentration of WSC is160 mg/ml and exhibited the strongest inhibition against S. aureus and E. coli, with clear area values of 7.47 mm and 6.70 mm, respectively. The best hand sanitizer formulation is HS3 (in addition of WSC 200 mg/ml) and the ability to inhibit S. aureus bacteria with a clear area value of 5.35 ± 0.57 mm and E. coli is 4.70 ± 0.07 mm. This study shows the potential of WSC from crab shells as a sustainable and effective antibacterial active ingredient in hand sanitizers, which requires further research on scalability and wider applications.